2007
DOI: 10.2143/ac.62.1.2019366
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between low T3 syndrome and NT-proBNP levels in non-cardiac patients

Abstract: In absence of overt cardiovascular disease, patients with low T3 syndrome present an increased concentration of NT-proBNP. These data suggest that low FT3 levels may be a contributing factor for the development of cardiac dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…Our findings in a heterogeneous patient group with different cardiovascular diseases are in concordance with a recent small report in 52 patients without cardiac or cardiovascular disease, in which low-T3 syndrome was associated with significant NT-pro-BNP elevation [17]. fT3 in that study was one of the strongest predictors of elevated NT-pro-BNP in multivariate analysis [17]. Our correlation of fT3 and NT-pro-BNP was clearly weaker, which might be due to the dominant influence of cardiac abnormalities on NT-pro-BNP values in our patient population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings in a heterogeneous patient group with different cardiovascular diseases are in concordance with a recent small report in 52 patients without cardiac or cardiovascular disease, in which low-T3 syndrome was associated with significant NT-pro-BNP elevation [17]. fT3 in that study was one of the strongest predictors of elevated NT-pro-BNP in multivariate analysis [17]. Our correlation of fT3 and NT-pro-BNP was clearly weaker, which might be due to the dominant influence of cardiac abnormalities on NT-pro-BNP values in our patient population.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, also fT3 values within the normal range were predictors for mortality and improved risk stratification in comparison to NT-pro-BNP alone. Our findings in a heterogeneous patient group with different cardiovascular diseases are in concordance with a recent small report in 52 patients without cardiac or cardiovascular disease, in which low-T3 syndrome was associated with significant NT-pro-BNP elevation [17]. fT3 in that study was one of the strongest predictors of elevated NT-pro-BNP in multivariate analysis [17].…”
Section: Discussionsupporting
confidence: 92%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 various cardiovascular disorders [23,24] including heart failure [13,25] , coronary artery disease [26] or patients with coronary artery bypass [17] . In addition, our results show that T3 levels were significantly lower in patients with risk factors of early mortality compared with low-risk patients.…”
Section: Tablementioning
confidence: 99%
“…There is still great uncertainty concerning the possible interactions between lower plasma fT3 or T3 levels and the major pathophysiological pathways implicated in critical cardiopulmonary distress. Low T3 serum concentrations have been associated with cardiac function and NT-pro-BNP levels in patients with heart failure [13,25,26] or acute coronary syndromes [12] . Recently, fT3 levels have been also correlated with echocardiographic and serum markers of myocardial dysfunction and injury including serum cardiac troponin I in patients with acute myocardial infraction [16,27] .…”
Section: Tablementioning
confidence: 99%
“…This finding has been associated with increased arterial stiffness in at least one study [117]. Another study showed that the median NT-proBNP concentration of patients with low T3 syndrome was significantly higher than in those with normal free T3, but the clinical significance of this finding remains uncertain [118]. Further studies are needed to determine the clinical utility, if any, of NT-proBNP determinations in patients with thyroid disease.…”
Section: Thyroid Diseasementioning
confidence: 99%